Rethinking capitalism : economics and policy for sustainable and inclusive growth / (Acc: P7453) - Jacobs, M. Mazzucato, M. (UK : Wiley Balckwell, 2016)
Western capitalism is in crisis. For decades investment has been falling, living standards have stagnated or declined, and inequality has risen dramatically. Economic policy has neither reformed the financial system nor restored stable growth. Climate change meanwhile poses increasing risks to future prosperity. In this book some of the world$1 (Bs leading economists propose new ways of thinking about capitalism. In clear and compelling prose, each chapter shows how today$1 (Bs deep economic problems reflect the inadequacies of orthodox economic theory and the failure of policies informed by it. The chapters examine a range of contemporary economic issues, including fiscal and monetary policy, financial markets and business behaviour, inequality and privatisation, and innovation and environmental change. The authors set out alternative economic approaches which better explain how capitalism works, why it often doesn$1 (Bt, and how it can be made more innovative, inclusive and sustainable. Outlining a series of far-reaching policy reforms, Rethinking Capitalism offers a powerful challenge to mainstream economic debate, and new ideas to transform it. s
Includes bibliographical references and indexes.